2020
DOI: 10.31234/osf.io/kvesm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Creative Lockdown? A Daily Diary Study of Creative Activity During Pandemics

Abstract: The current COVID-19 pandemic is influencing our lives in an enormous and unprecedented way. Yet while this impact is being intensively studied with regard to a broad range of health, social, and psychological aspects, the effects of COVID-19 for creativity have been overlooked. Here, we explore COVID-19-lockdown’s consequences for creative activity. To this end, we relied on two extensive diary studies. The first, held in March 2019 (pre-pandemic), involved 78 students who reported their emotions and creativi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…Creativity changes were first estimated based on a self-report of a change as perceived by each participant (SCC). SCC revealed that participants experienced being more creative during the lockdown than the period before, which is consistent with previous studies that reported an increase in everyday creativity during the lockdown 32,33 . SCC correlated with the BFI-O score, which captures a basal creative personality trait 38,39 and which was in the range of what has been previously observed 40 .…”
Section: Creativity During the Lockdownsupporting
confidence: 91%
See 1 more Smart Citation
“…Creativity changes were first estimated based on a self-report of a change as perceived by each participant (SCC). SCC revealed that participants experienced being more creative during the lockdown than the period before, which is consistent with previous studies that reported an increase in everyday creativity during the lockdown 32,33 . SCC correlated with the BFI-O score, which captures a basal creative personality trait 38,39 and which was in the range of what has been previously observed 40 .…”
Section: Creativity During the Lockdownsupporting
confidence: 91%
“…Several studies reported how the pandemic and lockdown had increased psychological distress, mood disorders, loneliness, and anxiety [1][2][3][4][5] , with a potential negative impact on creativity. Nevertheless, the few existing scientific studies that explored creativity during the COVID-19 pandemic have indeed suggested that the lockdown period facilitated everyday creativity 32,33 or that creative abilities could help people dealing with the situation and improve their wellbeing 3,34,35 . However, those studies did not assess how creativity changes related to environmental, contextual, or emotional changes.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that only social identity affirming behaviours had a significant impact on QoL. In fact, as previously discussed, the involvement in creative behaviors could have a positive impact on mental health and QoL during a lockdown period ( Kanekar & Sharma, 2020 ; Karwowski et al, 2020 ).…”
Section: Discussionmentioning
confidence: 74%
“…In order to overcome perceived threats and contagion fear in a social distancing context, people tried to cope by carrying out behaviors that affirm social (e.g., interacting virtually online with cultural groups sharing media about life before COVID-19) and national identity (e.g., cooking typical recipes; Jaspal & Nerlich, 2020 ; Kachanoff et al, 2020 ). These behaviors may well act as strategies which help to cope with the fear of contagion, transiently enhancing well-being and therefore QoL ( Karwowski et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…the function of shopping is to ensure oneself of the necessary ingredients to stay alive) [72]. People became task-oriented, yet were less to engage in creative thinking which is primarily driven primarily by enjoyment and meaning in the activities [74,75]. Consequently, the form of the activities did not leave enough room for aspects of meaning, such as shopping together for fun.…”
Section: Discussionmentioning
confidence: 99%